Hepatitis A outbreak affecting men who have sex with men (MSM) in central Argentina, occurred in July 2017-April 2018, later than the European outbreak - Mariojouls, Jorge (2019)
During June-2016 - May-2017, several outbreaks of HA were recorded in Europe, especially described in MSM. In our area since July-2017, an increase of hepatitis A (HA) notification was reported. In order to understand the unusual increase of cases occurred in the central region of Argentina, the aim of this study was to describe, characterize and contextualize epidemiologically the HA outbreak occurred this area, until April 2018. Study designHA cases (positive anti-HAV IgM) obtained from the calendar week 29/2017 in which the first case of MSM was recognized were included in our study. HAV RNA detection and molecular characterization was performed from serum samples and / or stool by RT - PCR of VP1 / 2A genomic region (360bp).ResultsOf the 32 cases notified, 87.5% of them were unvaccinated men and 69.6% were MSM (mean age 31.9 years). All MSM associated HAV sequences were genotyped as IA, and clustered with the VRD 521-2016 strain, responsible of causing outbreaks mostly in MSM in Europe since mid-2016. As a consequence of the implementation of immunization in children, and the improvement in socio-economic, hygienic and sanitation factors, young adults are becoming increasingly susceptible to HAV infections. Here we add evidence in South America to the HA outbreaks described worldwide among young MSM, demonstrating the need to reinforce official policy of vaccination, in this group and adjust epidemiological surveillance, catch-up vaccination for adolescents, young adults and immuno suppressed patients.